2020
DOI: 10.1021/acs.nanolett.0c02551
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing of Nanoporous Gold Under Ambient Conditions

Abstract: Failure of a material is an irreversible process since the material loses its original characteristics and properties. The catastrophic brittle failure under tensile stress of nanoporous gold (np-Au) with a bicontinuous open-cell structure makes impossible otherwise attractive applications. Here, we first demonstrate a self-healing process in tensile-fractured np-Au to overcome the limit of fragility via mechanically assisted cold-welding under ambient conditions. The self-healing ability of np-Au in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…We fabricated the nanoporous electrodes using a dealloying process with Ag:Au alloys. [38,39] The pore size in these electrodes can be tuned by adjusting the ratio of Ag to Au. We used two approaches-thermal annealing [28] and electrochemical coarsening 29 -to adjust the average pore and ligament sizes in our nanoporous structures.…”
Section: Characterization Of Aptamer-immobilized Nanoporous Electrodesmentioning
confidence: 99%
“…We fabricated the nanoporous electrodes using a dealloying process with Ag:Au alloys. [38,39] The pore size in these electrodes can be tuned by adjusting the ratio of Ag to Au. We used two approaches-thermal annealing [28] and electrochemical coarsening 29 -to adjust the average pore and ligament sizes in our nanoporous structures.…”
Section: Characterization Of Aptamer-immobilized Nanoporous Electrodesmentioning
confidence: 99%
“…Figure 4e shows a TEM image of the assembled AuAg NSs. The NS lattice fringes of the (200) and (111) planes are 0.20 and 0.24 nm, respectively, which can be determined based on the HRTEM analysis in Figure 4f.…”
Section: Synthesis Of Nanoribbons and Epitaxial Growthmentioning
confidence: 99%
“…In addition to assembling the metal NNW based integrated logic circuits and nanodevices, nanowelding can also be used for self-healing when cracks, damages, and scratches appear. [198][199][200] It was found that the predamaged Au nanomeshes induced by deformations can be recovered through cold welding induced by cyclic compression, stretching or random deformations. [198] The rewelding of fractured Au NWs is beneficial to the conductivity.…”
Section: Self-healing Assited By Nanoweldingmentioning
confidence: 99%
“…Formation of an Ag nanowire network via the three ways was also discovered by Peng et al, 11 demonstrating nanowelding for a room temperature pressureless Cu a School of Intelligent Manufacturing and Control Engineering, Shandong Institute substrate and Ag nanowire paste at the same time. Threedimensional reconstruction of self-healed nanoporous Au by Gwak et al 12 further stressed the great importance of different contact modes in the recovery and bottom-up synthesis of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%